Prospective Teachers’ Perceptions of Influential Teacher Qualities - Daniel J. Bergman (The Advocate, 2018)
While much has been written regarding elements of “good” teachers, little exists with respect to qualities of influential teachers. Prospective science teachers (N = 98) completed a survey identifying and describing influential teachers in their own lives. In addition to demographic data, qualitative content analysis of narratives excavated common themes. The seven most frequent attributes of influential teachers were passion, rapport, pedagogy, time, high expectations, fun, and helpful. Implications for teacher education and research include synergistic combinations of these traits, alignment with literature on effective teaching, development of professional dispositions, and more.
Keywords: Preservice Teachers; Teacher Influences; Professional Dispositions